Too Precarious By Half: Understanding Indonesia’s Refusal Of Ex-ISIS Indonesian Citizens’ Return In Favor Of Its Security Interest - Manullang, Abel Josafat; Maulana, Ana; Gultom, Yosua Saut Marulitua (Journal Of Middle East and Islamic Studies, 2024)
The problems stemming from ISIS does not only come during the pinnacle of its campaign of terror, rather it is also available following its downfall. One prominent example would be the many former ISIS members who now wish to return home. Indonesia, having some of its citizens joining ISIS back then, made the stern call to deny their return. To this day, debates and discussions over it still remain to this day. Against that backdrop, the article seeks to explain why the aforementioned decision was made by taking into account the security dimension of the matter. In carrying out this undertaking, the writers made use of both primary and secondary data procured from the internet under the qualitative research method. The forthcoming analysis is also supported by relevant concepts and theories like national security and rational choice theory. The paper begins with an overview of the issue at hand that entails ISIS's downfall along with the fate of Indonesia citizens who partook in ISIS's campaign of terror. Additional discussion is also provided as to how such a decision stands amidst Indonesia's commitment to the global human rights regime and why it still pales in importance to said security considerations.